The Implementation of Social Work Practice with Children in Indonesia - Ellya Susilowati; Krisna Dewi; Meiti Subardhini (Asian Social Work Journal, 2017)
This study aimed at examining the implementation of social work practice with children in Indonesia. The research used qualitative method with a case study on nine informants who were Social Workers carrying out the task of handling children cases in the city of Bandung, Indonesia. The results showed that Social Workers had started to implement social work practice with children in handling 44 cases of children, but, according to social work practice standards with children as defined by NASW (2013) and based on pragmatic perspectives of social work with children according to Petr.CG 2004), it was not optimal. The implementation of social work practice with children was seen from aspects of practice: 1) building relationships with children should had been done with a consideration to the children’s ages; 2) assessment with children should had already used 'tools' assessment; 3) preparation of intervention plans was less involving children and families; 4) interventions was less responding to the needs of children and less applying behavior change techniques; and 5) the evaluation had not been implemented and supervised. Based on the research findings it is recommended for: 1) Training Center to provide training on the perspective of social work practice with children for Child Social Workers; and 2) Directorate of Child Welfare of the Ministry of Social Affairs to facilitate the implementation of supervision on child social work practice by supervisors; 3) Child Study Center to conduct further study on child social work practice based on clusters of child problems.